Produktivitas Ulat Sutera (Bombyx mori L.) Ras BS-09 di Daerah Tropis - Estetika, Y.; Endrawati, Y. C. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
Silkworm is a cold-blooded animal (poikiloterm) so that environment conditions greatly affect their growth. In China, silkworms rearing in the highlands with cool conditions. However, Indonesia is a tropical country with diverse topography conditions and some of them are low altitude areas below 250 m above sea level (asl). This study examined the productivity of silkworms in altitude of 250 m asl. The material used silkworm seedlings from the Silkworm Breeding Center (PPUS) Soppeng and Candiroto, and using 2 different types of mulberry leaf feed (Morus multicaulis and Morus cathayana). Both PPUS have different climatic and altitude conditions. Soppeng at an altitude less than 300 meters asl and Candiroto at a higher one. The results showed that silkworm from Soppeng with fed M. multicaulis was significant different (P<0.05) than other treatments in almost all parameters (consumption, weight of larva, quantity and quality of cocoon shell). The result indicated silkworm Soppeng breed with M. multicaulis have good performance either cocoon shell productions and qualities in Tropic (especially rearing at altitudes around 250 m asl).